Tandem CAR T-cells targeting CD19 and NKG2DL can overcome CD19 antigen escape in B-ALL - Bolsée, Jennifer; Violle, Benjamin; Jacques-Hespel, Céline; Nguyen, Thuy; Lonez, Caroline; Breman, Eytan (Frontiers in Immunology, 2025)
IntroductionChimeric antigen receptor (CAR) T-cell therapies have achieved remarkable success in treating B-cell malignancies, including acute lymphoblastic leukemia (B-ALL). However, despite high remission rates, relapse due to antigen escape remains a significant challenge. To overcome this, designing CAR T-cells targeting multiple cancer antigens simultaneously is a promising strategy. NKG2D ligands (NKG2DL) are eight stress-induced ligands expressed by cancer cells but largely absent on healthy cells.Methods and ResultsWe hypothesized that simultaneous targeting of NKG2DL (using the NKG2D extracellular domain) and CD19 can prevent CD19 antigen escape and improve long-term remission rates in B-ALL patients. We developed three tandem CARs targeting both CD19 and NKG2DL and demonstrated that two tandem candidates were highly effective against both CD19+ and CD19- cancer cell lines. Importantly, when compared to CD19 CAR T-cells, tandem CAR T-cells exhibited comparable cytokine secretion, cytolytic activity and proliferation levels when incubated with cancer cells expressing CD19 and were still effective when incubated with cancer cells lacking CD19. Moreover, T-cells transduced with the selected CD19/NKG2DL tandem CAR were functional against CD19+ primary B-ALL samples and controlled tumor growth in a highly challenging xenograft model representing a CD19- B-ALL relapse.DiscussionThese findings provide proof-of-concept that NKG2D-based tandem CARs offer a promising approach to overcome antigen escape and enhance anti-tumor efficacy in B-cell malignancies.